2010
DOI: 10.2337/dc10-0275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glutamine on Glycemic Control During and After Exercise in Adolescents With Type 1 Diabetes

Abstract: OBJECTIVETo investigate if oral glutamine ameliorates exercise and postexercise nighttime hypoglycemia in type 1 diabetic adolescents.RESEARCH DESIGN AND METHODSTen adolescents (15.2 ± 1.4 years [SD], A1C 6.9 ± 0.9%) on insulin pumps were studied. The subjects were randomized to receive a glutamine or placebo drink pre-exercise and at bedtime (0.25 g/kg/dose). A 3:00 p.m. exercise session consisted of four 15-min treadmill/5-min rest cycles. Pre-exercise blood glucose was 140–150 mg/dl and was monitored throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
4
9
0
Order By: Relevance
“…Consistent with an earlier preliminary report [17], the present study demonstrates that GLN supplementation acutely increases the likelihood of postexercise, overnight hypoglycemia in adolescents with T1D. These data demonstrate that after strenuous exercise, GLN decreases glucose production or increases glucose utilization in T1D.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with an earlier preliminary report [17], the present study demonstrates that GLN supplementation acutely increases the likelihood of postexercise, overnight hypoglycemia in adolescents with T1D. These data demonstrate that after strenuous exercise, GLN decreases glucose production or increases glucose utilization in T1D.…”
Section: Discussionsupporting
confidence: 92%
“…BG was titrated (129 ± 37 mg/dL) before exercise at 1500 h. Children were randomized to receive a drink containing either GLN (0.25 g • kg −1 •dose −1 ) or PL (calorie- and nitrogen-free) before exercise, at bedtime, and at 0530 h the following morning. The dose (0.75 g • kg −1 • 24 h −1 ) was chosen to match doses used in clinical trials in other settings [1113] and found to affect BG in our earlier study [17]; such doses are of the same order of magnitude as endogenous GLN production (348 μmol • kg −1 • h −1 , i.e., 1.2 g • kg −1 • d −1 ) [18]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized crossover pilot study in children with type 1 diabetes has investigated whether oral Gln could improve hypoglycaemia during exercise and overnight after exercise [229]. Ten adolescents (mean age 15.2 ± 1.4 y) on insulin pumps were randomized to receive a drink containing Gln or placebo preexercise and at bedtime (0.25 g/kg/dose).…”
Section: Resultsmentioning
confidence: 99%